Good faith in contract law : A comparative survey - Fong, C.M. (2006)
The law of contracts has generally been understood in the context of the capitalistic market. Encouraged by the eighteenth century pre-market economy, ideas of freedom of contract bloomed in the nineteenth century laissez faire period. Among the results of this period were standard form contracts, exclusion clauses and a strict adherence to the construction of the terms agreed upon. However, the law of contract has undergone much transformation. It is submitted that what may be described as a former traditional treatment of contract law has now been gradually replaced by a modern treatment of contract law. This modern period of contract law has seen the rise in the use of doctrines such as unconscionability' and reasonableness' to provide more equilibrium and fairness between contracting parties. Besides these, the principle of unjust enrichment has advanced the law of restitution to provide restitutionary relief.' and in equity, the fiduciary and constructive trust principle has made equitable remedies attractive in the commercial world.4. This paper focuses on yet another modern armour in the law of contract, that is, the doctrine of good faith. Unlike the other doctrines that have by now, found some acceptance, the doctrine of good faith has raised both optimism and pessimism by virtue of its rather amorphous nature. Despite the skeptics, the concept of good faith is already incorporated in significant international instruments. The paper will set out the position of good faith in the civil law system where it is well established, its treatment in the United States and its incorporation in international instruments. In the United Kingdom, the concept of good faith is not accepted and the views for and against good faith will be considered. In Australia, there have been significant developments in advancing good faith in contract law. Finally, this paper will consider the position in Malaysia.